Do we need a uniform regulatory system for biobanks across Europe? - Kaye, J (2006)
Within Europe, there is currently no uniform regulatory system that applies to human biobanks used for genetic research purposes. This has resulted in considerable variation in the national law that applies to the use of DNA samples, personal information and medical records in the countries across Europe. This could result in a situation where researchers collaborating across Europe may be operating unlawfully if they share research data and samples across borders where different laws are in operation. There are also concerns that the lack of standardised guidelines inhibits cooperation among researchers across Europe but also restricts the sharing of DNA samples and information across national borders, which is problematic for multinational companies and institutions carrying out collaborative research. Ultimately, the lack of a uniform regulatory system may have implications for the viability and long-term competitiveness of collaborative European research. The purpose of this paper is to discuss some of the preliminary issues that would need to be considered before such a regulatory system for biobanks could be developed within Europe.